Intensitas dan Prevalensi Cacing Ektoparasit Pyragraphorus hollisae pada Ikan Bawal Bintang (Tranchinotus blochii) di Perairan Lampung, Sumatera, Indonesia - Rizhar Eman Karunia Akbar; Sri Subekti; Nunuk Dyah Retno Lastuti (Airlangga University, 2022)
Pomfret (Tracinotus blochii) is a new commodity currently the mainstay of Indonesian marine aquaculture. Pomfret's exports totaled 2,150 thousand tons in 2018. From 2017 to 2018, this number increased by 100 percent from the export volume produced in Indonesia, which was 1,075 thousand tons. Of course, there are problems that are frequently encountered in the development of cultivation, such as the attack of ectoparasite worms. In this study, the silver pompano was found to be infested with the Pyragraphorus hollisae worm. The purpose of this study is to determine the prevalence and intensity of the ectoparasite worm Pyragraphorus hollisae in silver pompano (Trachinotus blochii) in Lampung waters, Sumatra, Indonesia. This is an experimental laboratory study, and the study design is a cross-sectional study. The purposive sampling method was used to collect silver pompano. The intensity and prevalence of the P. hollisae ectoparasite worm that infested the silver pompano (Tracinotus blochii) in Lampung waters were the main parameters observed. Physical and chemical parameters are used as supporting parameters in this study. In the light category, the P. hollisae ectoparasite worm that infested silver pompano from Lampung waters had an intensity value of 1.38 individuals/head. The prevalence of P. hollisae worms in silver pompano (Trachinotus blochii) in Lampung waters was 86.7 percent in the usual category.